You & me : - Egan, Gerard (Brooks/Cole Pub. Co., 1977)
Focusing on skills of self-disclosure, listening, responding, challenging, and participating in groups, You and Me presents a systematic step-by-step procedure for increasing self-awareness and improving communication skills.